Anxious and depressive disorders in cancer patients with chronic pain at the stage of palliative care - Mukharovska Інна; Kalachov Олексій; Abdrjahimova Ціра; Kleban Катерина (Psychosomatic Medicine and General Practice, 2019)
The one of the leading stressful factor at the palliative stage of cancer is chronic pain that can caused arising mental disorders, especially affective and neurotic. The aim of the study was to study specificity of depressive and anxious states in cancer patient with different intensity of chronic pain. This is a conference abstract from the Scientific-practical conference "Psychosomatic medicine: science and practice". It is dedicated to anxious and depressive disorders in cancer patients with chronic pain at the stage of palliative care.